Effectiveness of 3D-printed orthoses for traumatic and chronic hand conditions: A scoping review. - T A M Oud (Public Library of Science (PLoS), 2021)
Background In the field of orthotics, the use of three-dimensional (3D) technology as an alternative to the conventional production process of orthoses is growing. Purpose This scoping review aimed to systematically map and summarize studies assessing the effectiveness of 3D-printed orthoses for traumatic and chronic hand conditions, and to identify knowledge gaps. Methods The Cochrane Library, PubMed, EMBASE, CINAHL, Web of Science, IEEE, and PEDro were searched for studies of any type of 3D-printed orthoses for traumatic and chronic hand conditions. Any outcome related to the effectiveness of 3D-printed orthoses was considered. Two reviewers selected eligible studies, charted data on study characteristics by impairment type, and critically appraised the studies, except for case reports/series. Results Seventeen studies were included: four randomized controlled trials, four uncontrolled trials, four case series and five case reports. Only three studies had a sample size >20. Impairments described were forearm fractures (n = 5), spasticity (n = 5), muscle weakness (n = 4), joint contractures (n = 2) and pain (n = 1). Four poor to fair quality studies on forearm fractures supported the effectiveness of 3D-printed orthoses on hand function, functionality, and satisfaction. One good quality study on spasticity demonstrated the effectiveness of 3D-printed orthoses on hand function. One poor quality pain study reported limited positive effects on satisfaction. Studies on muscle weakness and joint contractures showed no benefits. Conclusion Current literature addressing the effectiveness of 3D-printed orthoses for traumatic and chronic hand conditions consists primarily of small and poor methodological quality studies. There is a need for well-designed controlled trials including patient-related outcomes, production time and cost analyses.